PELAKSANAAN PIDANA KURUNGAN PENGGANTI DENDA DALAM KASUS TINDAK PIDANA KORUPSI DI WILAYAH PENGADILAN NEGERI PEKANBARU - Febria, Anggun; Erdianto, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In The provisions for criminal fines at extraordinary crime level are regulated in Law Number 20 of 2001 concerning Eradication of Corruption in Article 2 paragraph (1). However, the Corruption Law does not regulate the length of imprisonment in lieu of fines, the determination of the length of the substitute imprisonment refers to Articles 30 and 31 of the Criminal Code (KUHP). In practice, the implementation of fines is actually an alternative for the convicted person not to pay the fine so that the purpose of punishment to return state losses is not fulfilled. The purpose of writing this thesis is: First, knowing how to carry out imprisonment in lieu of fines in corruption cases. Second, to find out what are the benchmarks for judges in imposing imprisonment penalties in lieu of fines in corruption cases. Third, to find out how the difference in imprisonment in lieu of fines at the same amount of fines on the sense of justice and legal certainty.This type of research is sociological legal research (Social Lagal Research). This research is more specific to seeing the law in a real sense and examining how the law works in society by analyzing various literatures related to the problem being studied as well as interviews with the Head of Pidsus Section of the Pekanbaru District Prosecutor's Office and Pekanbaru District Court Judges.From the results of the research conducted, it can be concluded that, first, the implementation of imprisonment in lieu of fines is an option for the convict if he does not want to pay the fine and the prosecutor cannot force the convict to pay the fine. However, in 2019 there tended to be a balance between the defendant who chose to pay a fine and chose to serve imprisonment in lieu of a fine. Second, in the aspects of punishment, the judge in making his decision in addition to looking at the evidence and facts revealed in the trial, he also considers things that can alleviate and incriminate the accused. Third, judges in compiling their decisions must reflect justice, benefit and legal certainty. However, in practice, judges' decisions are often seen as not fulfilling a sense of justice and legal certainty.Keywords: Execution-Fines-Substitute Imprisonment